Efficacy of three anti-malarial regimens for uncomplicated Plasmodium falciparum malaria in Cambodia, 2009–2011: a randomized controlled trial and brief review - Dysoley Lek; Agus Rachmat; Dustin Harrison; Geoffrey Chin; Suwanna Chaoratanakawee; David Saunders; Didier Menard; William O. Rogers (Malaria Journal, 2022)
Abstract Background Anti-malarial resistance remains an important public health challenge in Cambodia. The effectiveness of three therapies for uncomplicated falciparum malaria was evaluated in Oddar Meanchey province in Northern Cambodia from 2009 to 2011. Methods In this randomized, open-label, parallel group-controlled trial, 211 subjects at least 5 years old with uncomplicated falciparum malaria were treated with 3 days of directly observed therapy: 63 received artesunate–mefloquine (AS/MQ), 77 received dihydroartemisinin–piperaquine (DHA/PPQ), and 71 received atovaquone–proguanil (ATQ/PG). The subjects were followed for 42 days or until recurrent parasitaemia. Genotyping of msp1, msp2, and glurp among individual parasite isolates distinguished recrudescence from reinfection. Pfmdr1 copy number was measured by real-time PCR and half-maximal parasite inhibitory concentrations (IC50) were measured in vitro by 48-h isotopic hypoxanthine incorporation assay. Results The per-protocol PCR-adjusted efficacy (95% confidence interval) at 42 days was 80.6% (70.8–90.5%) for AS/MQ, 97.2% (93.3–100%) for DHA/PPQ, and 92.9% (86.1–99.6%) for ATQ/PG. On day 3, 57.9% remained parasitaemic in the AS/MQ and DHA/PPQ arms. At baseline, 46.9% had microscopic Plasmodium falciparum gametocytaemia. Both recurrences in the DHA/PPQ arm lost Pfmdr1 copy number amplification at recrudescence. All four recurrences in the ATQ/PG arm were wild-type for cytochrome bc1. One subject withdrew from the ATQ/PG arm due to drug allergy. Conclusions This study was conducted at the epicentre of substantial multi-drug resistance that emerged soon thereafter. Occurring early in the national transition from AS/MQ to DHA/PPQ, both DHA/PPQ and ATQ/PG had acceptable efficacy against uncomplicated falciparum malaria. However, efficacy of AS/MQ was only 80% with apparent mefloquine resistance based on elevated Pfmdr1 copy number and IC50. By 2009, there was already significant evidence of artemisinin resistance not previously reported at the Northern Cambodia–Thai border. This study suggests the basis for early development of significant DHA/PPQ failures within 3 years of introduction. Artemisinin resistance likely occurred on the Northern border concurrently with that reported along the Western border in Pailin. Trial registration This legacy trial was conducted prior to International Committee of Medical Journal Editors’ requirements for preregistration on ClinicalTrials.gov. The full protocol has been provided.